Strategi Pengelolaan Persampahan Kabupaten Pasaman Barat - Edison Zelmi; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin; Fajar Agung Mulia (Jurnal Sains dan Ilmu Terapan, 2024)
Waste management in West Pasaman Regency encounters significant challenges, including limited infrastructure, low public awareness, and inadequate coordination among agencies. This study aims to analyze the factors influencing waste management in the region using the Interpretive Structural Modeling (ISM) approach. The findings indicate that Government Policy, Waste Management Infrastructure, and Budget Allocations for Waste Management are the most influential factors in the waste management system. Conversely, factors such as Public Awareness and Private Sector Participation are more reliant on existing policies and infrastructure. Furthermore, this analysis elucidates the causal relationships among these factors and emphasizes the complex interactions inherent in waste management. Based on these insights, it is recommended that waste management policies be reinforced, budgets be augmented, and both infrastructure and community education programs be enhanced to achieve more effective and sustainable waste management. This study contributes to the formulation of a more integrated waste management policy, grounded in a comprehensive understanding of the interplay of factors at the local level.